Cell-penetrating peptide-based nanovehicles potentiate lymph metastasis targeting and deep penetration for anti-metastasis therapy - Hu, Haiyan (Theranostics, 2018)
Lymph metastasis is a vital pathway of cancer cell dissemination, and insidious lymph node metastasis increases the risk of distant cancer metastasis. Current therapies for lymph metastasis are largely restricted by limited targeting and penetration capacity. Herein, we report that an r9 cell-penetrating peptide-based cabazitaxel nanovehicle (r9-CN) displays prominent lymph metastasis targeting and deep penetration ability after intravenous injection for effective anti-metastasis therapy. Methods: The r9-CN and CN nanovehicles were prepared by thin film dispersion, using DSPE-PEG2000 as the nano-carrier material and cabazitaxel as the model drug to fabricate r9-modified nano-micelles by self-assembly. The morphology, size, and stability in physiological solutions of r9-CN and CN were characterized. The targeting, biodistribution, deep penetration, and therapeutic efficacy of r9-CN and CN were systematically explored in vitro and in vivo. Results: The r9-CN nanovehicle consists of homogeneous particles with a mean diameter of 13 nm and zeta potential of +0.75 mV. Compared with the nanovehicle lacking the r9 peptide (CN), r9-CN exhibits long retention and deep penetration in the tumor mass, and considerably enhances accumulation and flexible permeation in metastatic lymph nodes, thereby notably suppressing primary tumor growth, lymph node metastasis, and distant lung metastasis. Conclusion: The cumulative findings reveal that r9-CN offers a promising delivery platform, enabling efficient lymph metastasis targeting and deep penetration for effective anti-metastasis therapy.